FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI EKS KARISIDENAN SEMARANG (Students' Journal of Accounting and Banking, 2013)
In line with the policy of regional autonomy through the Law No. 22 Year 1999 on Regional Government and Law No. 25 of 1999 on Fiscal Balance between the Central Government and the Regions, as amended by Act No. 32 of 2004 on Regional Government and Law law Number 33 of 2004 on Fiscal Balance between the Central Government and Local Government.The purpose of this study was to analyze the influence of population on land and building tax revenue in the former residency of Semarang. Analyze the effect of Gross Regional Domestic Product (GRDP) of the property tax revenue in Semarang Residency Ex. Analyze the effect of inflation on property tax revenues in the residency of Semarang Ex. As for the population in this study is the population in this study is Grobogan, Demak, Semarang regency, Kendal, Semarang and Salatiga. The sample used in this study is Grobogan, Demak, Semarang, Kendal, Semarang and Salatiga with the data from 2005 to 2011. Analysis tool used is multiple linear regressio There results showed that the effect of population on the acceptance of the United Nations in Grobogan, Demak, Semarang, Kendal, Salatiga and Semarang. No influence on the GDP of the United Nations acceptance Grobogan, Demak, Semarang, Kendal, Salatiga and Semarang. It means that any increase in GDP will increase UN revenue. No influence on theKeywords: United Nations, Population, GDP, Inflation